Formalism of School Knowledge from the Standpoint of the Activity Approach in Psychology: Research Prospects - Anastasia N. Sidneva (Вестник Московского университета. Серия 14: Психология)
Background. The formal, shallow assimilation of school knowledge is studied in psychological and pedagogical science under different terms, each of which has a separate research area. Naive concepts, a “superficial” learning approach, functional illiteracy, the gap between knowledge and application — within the framework of this far from complete list, the same phenomenon of formalism is studied. In fact, overcoming the formalism is one of the key tasks of modern school education. Objective. This paper compares different approaches to the analysis of the functional meaning of formalism mistakes, highlights the specifics of the activity approach to student mistakes, and describes the prospects for this approach. Methods. In order to study the formalism of knowledge within the approaches, outlined above, functional analysis was applied as “the analysis of a mental phenomenon in relation to the performed socially-determined function”. Results. The analysis shows that the errors of the formalism of school knowledge in most approaches are viewed negatively as something that must be avoided. However, from the point of view of the activity-based approach, the formalism mistakes are a necessary type of feedback for teachers and programme developers, pointing to specific areas of modification of the learning process, thus acting as one of the most important means of identifying key psychological and pedagogical conditions for the effective assimilation of new concepts. Conclusions. Based on the work carried out, the need for further research of formalism within the framework of the activity approach is substantiated — an analysis of existing curricula from the perspective of which specific conditions for effective assimilation and development are supported in them and which are not. The theoretical significance of the proposed approach to the study of the formalism of knowledge is to highlight the prospects for the development of modern psychology of teaching.